Implementation of Spirituality Value in the Company - Jondar, Aloysius; Sampaleng, Donna; Halim, Verina (Al-Hayat: Journal of Islamic Education, 2023)
This study explores the value of spirituality in the business organization practices of PT Emdeki Utama, Gresik, East Java. The method used is qualitative with a case approach. Data collection uses an interview approach with management and customers. Data analysis uses source triangulation as a result of the research. So, from the effects of his study, found the value of work spirituality at PT Emdeki, especially openness. The value communicated here from the start is more openness between office workers. This shows that management considered open systems design when building this office. The company has tested this working process without incident. The company always calls for being honest with yourself and honest with others. Every employee works hard to maximize their skills. Employees develop their capabilities and potential. The company has to manage all of this. Emdeki also thanks its customers for their honest, conscientious and thorough work. The commitment of customers and employees to work with Emdeki is unquestionable. Emdeki asks to work with honesty, dedication and hard work. This research is the author's work based on the author's point of view when exploring problems in the field. This does not mean there are no deficiencies, for the authors still expect suggestions and criticisms to build scientific developments in this country.